The High-Level Syntax of the Versatile Video Coding (VVC) Standard - Wang, Ye-Kui; Skupin, Robert; M. Hannuksela, Miska; Deshpande, Sachin; Hendry; Drugeon, Virginie; Sjöberg, Rickard; Choi, Byeongdoo; Seregin, Vadim; Sanchez, Yago; M. Boyce, Jill; Wan, Wade; et al. (IEEE Transactions on Circuits and Systems for Video Technology, 2021)
Versatile Video Coding (VVC), a.k.a. ITU-T H.266 | ISO/IEC 23090-3, is the new generation video coding standard that has just been finalized by the Joint Video Experts Team (JVET) of ITU-T VCEG and ISO/IEC MPEG at its 19th meeting ending on July 1, 2020. This paper gives an overview of the VVC high-level syntax (HLS), which forms its system and transport interface. Comparisons to the HLS design in High Efficiency Video Coding (HEVC) and Advanced Video Coding (AVC), the previous major video coding standards, are included. When discussing new HLS features introduced into VVC or differences relative to HEVC, the reasoning behind the design differences and the benefits they bring are described. The HLS of VVC enables newer and more versatile use cases such as video region extraction, composition and merging of content from multiple coded video bitstreams, and viewport-adaptive 360° immersive media.